Eurasian Security from the Perspective of the Concept of Information-Psychological and Cognitive Confrontation - I. F. Kefeli; R. S. Vykhodets (Евразийская интеграция: экономика, право, политика, 2023)
The article is devoted to the analysis of the cognitive aspect of information and psychological confrontation in the Eurasian space, as well as to the study of the evolution of ideas that are currently commonly referred to by the term “information and psychological and cognitive confrontation”.Aim. To identify the specifics of ensuring Eurasian security in the perspective of the concept of information-psychological and cognitive confrontation.Tasks. To identify the information and psychological component in the CSTO collective security strategy, to analyze practical steps at the CSTO level in the field of countering destructive information influence, to determine the regulatory, political and organizational prerequisites for the formation of the CSTO collective information and psychological security system.Methods. The research uses both general scientific methods: analysis, synthesis, induction, and a number of special methods and approaches: comparative analysis, methodology of critical geopolitics, content analysis, informational and historical approaches.Results. The study showed that the formation of the modern concept of information-psychological and cognitive confrontation was significantly influenced by theoretical and applied research related to the understanding of the role of psychological operations and the use of special means of influencing the human psyche in modern military conflicts, as well as scientific developments in the field of studying modern methods of manipulation and propaganda, expanding the arsenal of means of hybrid conflicts, the weaponization of digital technologies, the emergence of new dimensions of international conflicts. Its subject includes systems and tools for the formation of public opinion, the peculiarities of human perception of information, as well as the whole range of methods and means of influencing public opinion and the psyche of an individual in peacetime and in combat conditions with the use of special information and psychological operations of strategic, tactical, operational level, as well as soft power tools.Conclusions. Today, more and more countries of the world are paying increased attention to the issues of ensuring information and psychological security. The desire of the post-Soviet states to preserve the political, economic and socio-cultural ties developed during their life in a single state, within the framework of new integration formats, the CIS, the EAEU, the CSTO, is increasingly faced with the problem of choosing a vector of foreign policy. Therefore, combining national interests and collective efforts to develop and conceptualize a unified approach to ensuring information and psychological security at the level of the main Eurasian cooperation formats, such as the EAEU, the CSTO and the SCO, is a priority task in the modern conflict realities of world politics.